Adjuvant potential of selegiline in treating acute toxicity of aluminium phosphide in rats. Issue 1 (21st February 2019) - Maleki, Adeleh; Hosseini, Mir‐Jamal; Rahimi, Nastaran; Abdollahi, Alireza; Akbarfakhrabadi, Amir; Javadian, Nina; Amiri, Shayan; Behnoush, Behnam; Dehpour, Ahmad Reza
Abstract: Aluminium phosphide (AlP) is a highly toxic substance with a high mortality rate and no effective antidote. Once exposed to the moisture and acidic conditions of the stomach, AlP releases toxic phosphine (PH3 ) gas, which results in severe toxicity in poisoned subjects. Selegiline is a monoamine oxidase inhibitor with antioxidant and anti‐apoptotic properties, which is mostly prescribed for the treatment of mood disorders and Parkinson's disease. Since AlP has detrimental effects on cardiac physiology and mitochondrial function, we tested the protective effects of acute selegiline treatment on cardiac mitochondrial function, redox status and electrocardiographic parameters in rats after AlP poisoning. To do this, AlP was given to rats by gavage to induce toxicity. Selegiline was injected intraperitoneally in the treatment groups 1 hour after AlP poisoning. Selegiline treatment after AlP intoxication was not associated with a significant difference in the mortality rate of animals. However, selegiline reduced oxidative stress (decreased the reactive oxygen species and malondialdehyde) and increased glutathione in the cardiac tissue of rats exposed to AlP. Further, the mitochondrial membrane potential (ΔΨm) collapse reversed after treatment with selegiline. Selegiline also improved the electrocardiographic (ECG) parameters and enhanced heart rate. The histopathological evaluation revealed that selegiline eliminated the inflammation and injuries induced by AlP in the stomach and duodenum, as well as cardiac tissue. In conclusion, selegiline treatment can ameliorate the AlP‐induced cardiac and gastrointestinal injuries in rats via boosting redox status and mitochondrial function with no significant effect on survival. We suggest that using selegiline, apart from other clinical treatments, may improve the quality of treatment process for AlP toxicity.